Attitudes linguistiques et identités locales à Ṣanʻâ’ - Julien Dufour (Revue des Mondes Musulmans et de la Méditerranée)
In Ṣan‘â’s metropolis populations gather from all parts of Yemen, as well as from abroad. The voices in the street draw a linguistic picture of nearly all that can be heard in South Arabia and East Africa. Though the inhabitants share Arabic as a common language, one actually faces several distinct linguistic varieties. The Yemeni dialects are indeed so varied that intercomprehension cannot be readily expected without an adaptation of one’s speech habits. Techniques are developped for mutual understanding. In Yemen however it is not done to dress or speak as do dwellers of other provinces. Most of the time one does not even think of doing so.Is a neutral Yemeni dialect in the process of being formed ? Should we recognize the first traces of it in a modern Ṣan‘âni standard, which does exist up to a certain point ? This variety does not apparently gain ground in other regions. In Ṣan‘â’ however, a contemporary Ṣan‘âni neutrality seems to suit some of the inhabitants. With the demographic growth of the city, things are likely to change at a quick pace. The question will rest on the attachment to traditional, geographically defined social structures. Those who can afford it may like to shake them off. But for the time being most Yemenis are not in a position to do so.